The Long-Term Effects of Teachers' Gender Stereotypes on Labor Outcomes - Joan Jennifer Martinez (Institute of Labor Economics (IZA), 2025)
Teachers' stereotypical assessments widen the gender gap in earnings and formal sector employment after high school graduation, with lasting positive effects for men and shorter-term negative effects for women. Exposure to these assessments throughout high school disproportionately affects women's graduation, employment, working hours, and earnings during late adolescence and early adulthood. Implicit Association Test scores collected through a survey indicate that students from both genders internalize stereotypes about math and language skills. Stereotyped teachers also deter females from entering male-dominated occupations. I find no evidence that these assessments affect college application or enrollment outcomes for students, irrespective of gender.
Keywords: J16; J24; I24; J71; 330; gender stereotypes; gender pay gap; value-added; math